Oyegoke: Board Gender Diversity and Troubled Firms’ Profitability Evidence from Listed Manufacturing Firms in Nigeria - Oyegoke, Adebusola A.; Iyoha, Francis; Eriabie, Sylvester; Adeyemo, Kingsley A. (International Journal of Economics and Financial Issues, 2024)
This study aims to understand the weightiness of female board representation in facilitating the optimum performance of troubled firms toward their long-term sustainability. It examined BFGD as the fraction of female board members to the overall number of members on board. Data for the study were sourced from the audited financials of the selected troubled manufacturing firms from 2012 to 2022. Classification of firms into troubled was ascertained using the Altman Z scoring for manufacturing firms and analysed using the panel data regression method. The outcome of this study signified that the proportion of the female gender on board has an optimistic, albeit insignificant, influence on selected troubled firms’ performance indicator- ROA. This further buttresses the fact that BFGD is not a propelling force for enhancing troubled firms’ performance in Nigeria. Hence, this study recommended that female representation on board should not be merely symbolic or in conformity with societal inclusivity but instead be based on expertise, skills, experience, qualification, and exposure.